2020
DOI: 10.1016/j.ekir.2020.02.402
|View full text |Cite
|
Sign up to set email alerts
|

SAT-379 Glomerulonephritis Histopathological Pattern Change

Abstract: in five patients (62.5%). The most common de novo GN in those with a known NKD was calcineurin (CNI) induced thrombotic microangiopathy (TMA) in five patients (62.5%) while the most common de novo GN in those with unknown NKD were IgA nephropathy (4, 26.7%) and FSGS (4, 26.7%). Renal allograft biopsy was done mostly for proteinuria (18, 56.3%) followed by deterioration in renal function (9, 28.1%). Biopsy was done 17.5 (AE15) months post-transplant with the minimum duration being as low as six days. The mean p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…[15][16][17][18][19][20][21][22][23][24][25][26][27] In some of these studies, LN was the most common cause of secondary glomerulonephritis (GN), constituting between approximately 36%-72% of all secondary GN cases. [15][16][17][18][19][20][21]27 The two studies conducted in Oman showed that LN was the most frequent glomerular disease, occurring in approximately 30%-36% of all patients who had an available renal biopsy. 23,26 Proportion of patients with SLE that develop LN.…”
Section: Incidence and Prevalence Of Ln In The Arabian Gulf Regionmentioning
confidence: 99%
“…[15][16][17][18][19][20][21][22][23][24][25][26][27] In some of these studies, LN was the most common cause of secondary glomerulonephritis (GN), constituting between approximately 36%-72% of all secondary GN cases. [15][16][17][18][19][20][21]27 The two studies conducted in Oman showed that LN was the most frequent glomerular disease, occurring in approximately 30%-36% of all patients who had an available renal biopsy. 23,26 Proportion of patients with SLE that develop LN.…”
Section: Incidence and Prevalence Of Ln In The Arabian Gulf Regionmentioning
confidence: 99%